Impact of 18F-FDG PET/CT on the staging of patients with non-small cell lung cancer - Xuan, Ngo Minh; Huy, Huynh Quang (International Journal of Research in Medical Sciences, 2020)
Background: Non-small cell lung cancer (NSCLC) accounts for approximately 80% of new diagnoses of pulmonary carcinoma. This study investigated the correlation between 18 F-fluorodeoxyglucose uptake in computerized tomography integrated positron emission tomography and tumor size, lymph node metastasis, and distant metastasis in patients with NSCLC. Methods: The records of 318 NSCLC patients (220 male, 98 females; mean age 60.94 years) were evaluated retrospectively. Results: 278 cases were adenocarcinomas; 28 squamous cell carcinomas; and 12 large cell carcinoma. When the cases were categorized according to tumor size (group 1, ≤3 cm; group 2, >3 and ≤5 cm; group 3, >5 cm), the maximum standardized uptake value (SUVmax) was significantly lower in groups 1 and 2 compared with group 3 (p<0,001 for each). Considering all cases, tumor SUVmax was not correlated with age, gender or histopathological type. Lymph node metastases were seen in 250 cases: 80.2% of these were adenocarcinomas, 71.4% squamous cell carcinomas, and 58.3% large cell carcinomas. Neither lymph node involvement nor distant metastases were correlated with tumor SUVmax, although lymph node size was positively correlated with lymph node SUVmax (r=0.758; p<0.001). Conclusions: SUVmax was significantly associated with tumor size, but not with distant metastases or lymph node involvement. Therefore, SUVmax on positron emission tomography is not predictive of the presence of metastases.